Detection of faint secondary companions in spectroscopic binaries - Gonzalez, Jorge Federico (2024)
Context. Most known spectroscopic binaries are detected through the variation in the radial velocity of the primary star, while thespectral features of the secondary companion remain hidden in the noise.Aims. We present a novel technique for the spectroscopic detection of low-luminosity secondary companions of binary stars. Themain goal is to estimate the mass ratio even when the radial velocity of the secondary cannot be measured in individual spectra.Methods. The method aims to bring together all the spectral information of the secondary component into one single feature. In afirst step, a spectral disentangling technique is used in an automatic way for a grid of possible values of the mass ratio. Then, theresulting series of secondary component spectra are compared with a grid of synthetic templates with a technique inspired by spectralcross-correlations. By optimizing a function indicative of the significance of the secondary detection, the mass ratio and an estimateof effective temperature are derived.Results. We apply our method to different types of objects and observational datasets: three single-lined spectroscopic binaries inthe open cluster Blanco 1 observed at mid-spectral resolution, an early-type binary in the open cluster NGC 2362, and PX Vir, anF-type binary observed at high resolution for which the secondary companion had been detected in the infrared but not in the opticalspectral range. It is shown that from standard-quality spectral datasets it is possible to detect the secondary star in systems in whichthe secondary contributes less than 0.5–1.0% of the total flux.